Proteomics of Eosinophil Activation - Mosher, Deane F.; Wilkerson, Emily M.; Turton, Keren B.; Hebert, Alexander S.; Coon, Joshua J. (Frontiers in Medicine, 2017)
We recently identified and quantified >7,000 proteins in non-activated human peripheral blood eosinophils using liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) and described phosphoproteomic changes that accompany acute activation of eosinophils by interleukin-5 (Wilkerson et al., J. Proteome Res., 2016). These data comprise a treasure trove of information about eosinophils. We illustrate the power of label-free LC-MS/MS quantification by considering four examples: complexity of eosinophil STATs, contribution of immunoproteosome subunits to eosinophil proteasomes, complement of integrin subunits, and contribution of platelet proteins originating from platelet-eosinophil complexes to the overall proteome. We describe how isobaric labeling enables robust sample-to-sample comparisons and relate the 220 phosphosites that changed significantly upon treatment with interleukin-5 to previous studies of eosinophil activation. Finally, we review previous attempts to leverage the power of mass spectrometry to discern differences between eosinophils of healthy subjects and those with eosinophil-associated conditions and point out features of label-free quantification and isobaric labeling that are important in planning future mass spectrometric studies.